2014
DOI: 10.1103/physrevlett.113.087204
|View full text |Cite
|
Sign up to set email alerts
|

Phases of a Triangular-Lattice Antiferromagnet Near Saturation

Abstract: We consider 2D Heisenberg antiferromagnets on a triangular lattice with spatially anisotropic interactions in a high magnetic field close to the saturation. We show that this system possess rich phase diagram in field/anisotropy plane due to competition between classical and quantum orders: an incommensurate noncoplanar spiral state, which is favored classically, and a commensurate co-planar state, which is stabilized by quantum fluctuations. We show that the transformation between these two states is highly n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 18 publications
4
65
0
Order By: Relevance
“…For large spin values S ≫ 1, Starykh et al [30] have estimated (J/J z ) c1 and (J/J z ) c2 based on the dilute Bosegas expansion formalism, in which magnetic states in the vicinity of the saturation are described as BoseEinstein condensations (BECs) of dilute magnons via the Holstein-Primakoff transformation [32,33]. The values of (J/J z ) c1 and (J/J z ) c2 were determined at leading order in 1/S as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For large spin values S ≫ 1, Starykh et al [30] have estimated (J/J z ) c1 and (J/J z ) c2 based on the dilute Bosegas expansion formalism, in which magnetic states in the vicinity of the saturation are described as BoseEinstein condensations (BECs) of dilute magnons via the Holstein-Primakoff transformation [32,33]. The values of (J/J z ) c1 and (J/J z ) c2 were determined at leading order in 1/S as…”
Section: Introductionmentioning
confidence: 99%
“…has recently received increasing attention since the latest theoretical studies [29,30] indicated the possibility for the emergence of a new magnetic phase, named the π-coplanar or Ψ phase for J > J z > 0.…”
Section: Introductionmentioning
confidence: 99%
“…This canted ferromagnetic state exactly corresponds to the Bose -Einstein condensed state of the lattice bosons. Bose-gas description of spin model was extended to Heisenberg antiferromagnets in high magnetic fields, and the phase transitions between fully polarized and antiferromagnetic ordered states or the spin structures of the ordered states were discussed from the BEC point of view [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is interesting to note that a double-Q conical state, like the one described by Eq. (3), has been obtained below the saturation field of a spatially anisotropic TL model [28].…”
Section: Multi-q Instability Induced By a Single-ion Anisotropymentioning
confidence: 99%